1977
DOI: 10.1063/1.433849
|View full text |Cite
|
Sign up to set email alerts
|

A transient kinetics study of the reaction of CO with chemisorbed oxygen on platinum

Abstract: Transient pressure-jump experiments are reported in which the reaction between gas phase carbon monoxide and chemisorbed oxygen on polycrystalline platinum is followed using both CO2 decay and CO titration methods. The experiments are carried out at 540 °K and low pressures below 5×10−7 torr. From the data we conclude that the reaction between chemisorbed oxygen atoms and gas phase carbon monoxide is first order in CO pressure and, at high oxygen atom coverages, zero order in the adsorbed oxygen atom concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The zeolite and noble metal catalyst maintained operation at a steady state over the 1 h duration for sampling under autothermal conditions. 1152 www.chemsuschem.org ramping from 150-850 K. [11] CO 2 formation occurred through a combination of CO oxidation on platinum, as demonstrated by Hendriksen and Frenken in their scanning tunneling microscopy study of Pt {110} at 5 10 4 Pa and 425 K where Pt was observed to switch between metallic and oxidic states as a function of CO and O 2 pressures while effluent gases were monitored by mass spectrometry, and through water-gas shift reactions as demonstrated by Wheeler et al during autothermal CO conversion studies over Pt catalysts operating between 673-1273 K. [12][13][14][15] The product flow rates for the Pt-catalyzed reactions shown in Figure 2 provide further evidence for methane and CO generation occurring in the decarbonylation of the acetyl intermediate. At high E:H:O ratios, which cause lower reactor temperatures, there is a near 1:1 correlation between the total amount of carbon in CO and CO 2 versus carbon in CH 4 .…”
Section: Autothermal Ethanol Dehydration Experimentsmentioning
confidence: 99%
“…The zeolite and noble metal catalyst maintained operation at a steady state over the 1 h duration for sampling under autothermal conditions. 1152 www.chemsuschem.org ramping from 150-850 K. [11] CO 2 formation occurred through a combination of CO oxidation on platinum, as demonstrated by Hendriksen and Frenken in their scanning tunneling microscopy study of Pt {110} at 5 10 4 Pa and 425 K where Pt was observed to switch between metallic and oxidic states as a function of CO and O 2 pressures while effluent gases were monitored by mass spectrometry, and through water-gas shift reactions as demonstrated by Wheeler et al during autothermal CO conversion studies over Pt catalysts operating between 673-1273 K. [12][13][14][15] The product flow rates for the Pt-catalyzed reactions shown in Figure 2 provide further evidence for methane and CO generation occurring in the decarbonylation of the acetyl intermediate. At high E:H:O ratios, which cause lower reactor temperatures, there is a near 1:1 correlation between the total amount of carbon in CO and CO 2 versus carbon in CH 4 .…”
Section: Autothermal Ethanol Dehydration Experimentsmentioning
confidence: 99%